PERBEDAAN TRUST IN BRAND PRODUK ONLINE SHOP DENGAN KLINIK KECANTIKAN - Laras Indra Yani; Yanladila Yeltas Putra (Jurnal Riset Psikologi, 2019)
Differences trust in brand in product online shop and beauty clinic. This study suggest looking at the differences in trust in brand face skin care products online shop and beauty clinic. The design of this study is comparative quantitative with a study of a population of women who have used facial skin care product online shop and beauty clinic. The research sample was selected 69 people with a purposive sampling technique. Data collection was carried out using a scale of trust in brand collected 34 approved items arranged based on a likert scale. The data analysis technique used is the t-test different test analysis. The used is the t-test different test analysis. The results obtained p= 0,001 (p<0.05) and t values 0f 5.468, indicating the level of 0,05, which means the level of trust in brand is calculated on face skin care products online shop and beauty clinic.Perbedaan trust in brand produk online shop dengan klinik kecantikan. Penelitian ini bertujuan untuk melihat perbedaan trust in brand pada produk perawatan kulit wajah online shop dengan klinik kecantikan. Desain penelitian ini adalah kuantitatif komparatif, dengan populasi penelitian yaitu wanita yang pernah menggunakan produk perawatan kulit wajah online shop dengan klinik kecantikan. Sampel penelitian berjumlah 69 orang, dengan teknik purposive sampling. Pengumpulan data dilakukan dengan mengunakan skala trust in brand yang berjumlah 34 butir pernyataan yang disusun berdasarkan skala likert. Teknik analisis data yang digunakan adalah analisis uji beda ttest. Hasil penelitian didapatkan p=0,000 (p<0,05) dan nilai t sebesar 5.468 signifikan pada taraf 0,05, yang berarti terdapat perbedaan trust in brand pada produk perawatan kulit wajah online shop dengan klinik kecantikan.